Genetic Analysis of Cottonseed Protein and Oil in a Diverse Cotton Germplasm. Issue 5 (1st September 2016) - Campbell, B.T.; Chapman, K.D.; Sturtevant, D.; Kennedy, C.; Horn, P.; Chee, P.W.; Lubbers, E.; Meredith, W.R.; Johnson, J.; Fraser, D.; Jones, D.C.
Abstract : Historically, the primary objective of cotton ( Gossypium hirsutum L.) breeding programs was to improve the quantity and quality of cotton fiber. Because of the added value of cottonseed and its many uses, including a feed and human food source, there is interest in developing cotton breeding programs that focus improvement efforts simultaneously on cotton fiber and seed. Genetic analysis of cottonseed traits, such as protein and oil, is a prerequisite to building new joint fiber and seed cotton breeding programs. In this study, we conducted a genetic analysis of a diverse set of elite upland cotton germplasm for cottonseed protein and oil. Environment was responsible for a sizeable portion of the total variation for protein and oil, and genetics accounted for a larger portion of variation for oil than protein. Genotype × environment (G × E) interactions significantly impacted oil but not protein. Genotypic correlation analysis found a strong, negative relationship between protein and oil. Positive genotypic correlations were found for protein and several agronomic traits including lint yield; whereas, negative correlations were found between oil and lint yield along with other agronomic traits. Overall, results showed very little association between protein, oil, and fiber quality traits. These findings indicate that altering protein and oil seed composition will impact yield and yield component traits. However, alterations in seed composition should not impact fiber quality.